A Mobile Game-Based Application for Learning Collective Nouns of Animals: Nounimals - BAHARODDIN, NUR ALYA BATRISYIA; CHE DALIM, CHE SAMIHAH (Applied Information Technology And Computer Science, 2025)
Game-based learning enhances engagement by combining educational content with interactive play. Traditional methods of teaching collective nouns for animals often lack interactivity, and existing apps with static visuals and text-based quizzes make it difficult for primary school students to learn this knowledge. Hence, Nounimals is a mobile application that uses game-based learning technology has been developed by using a Multimedia Mobile Content Development methodology. The app targets primary school students, offering 2D visualizations, gamified quizzes, and real-time feedback to make learning collective nouns more engaging. The System Usability Scale (SUS) was used to evaluate user acceptance, resulting in a positive usability score of 71.5, which is above the average benchmark of 68 and indicates good usability and user satisfaction. Thus, Nounimals are suitable to be implemented in learning collective nouns of animals is expected.